2018
DOI: 10.1111/jphd.12278
|View full text |Cite
|
Sign up to set email alerts
|

Association between type of health insurance and children's oral health, NHANES 2011–2014

Abstract: Oral health outcomes, after adjusting for covariates, were similar for children with public and private health insurance. However, children in low-income families and with less educated parents had greater odds of untreated caries and dental caries, suggesting that initiatives focused on publicly insured populations may miss other vulnerable children of low socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The current study is also consistent with the results of other similar studies though context is different. For instance, Duffy et al (2018) found no significant difference in health status (e.g. dental caries) among for children aged 2-19 years by their insurance affiliations: public insurance, uninsured, private insurance, in the US.…”
Section: Discussionmentioning
confidence: 94%
“…The current study is also consistent with the results of other similar studies though context is different. For instance, Duffy et al (2018) found no significant difference in health status (e.g. dental caries) among for children aged 2-19 years by their insurance affiliations: public insurance, uninsured, private insurance, in the US.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of this study were also consistent with the studies in an international context. For instance, Duffy et al (2018) found no significant difference in the oral health status (e.g. dental caries) among children aged 2-19 years according to their respective insurance affiliations: public insurance, uninsured and private insurance, in the USA.…”
Section: Discussionmentioning
confidence: 94%
“…First, the migrant population has lower health insurance coverage and is not familiar with local oral health service policies [14] . Second, the utilization of dental care services is mainly related to family economic status [21], but most migrant families are poor. The treatment expense for oral diseases may be a large burden for lowincome families, and children from high-income families are more likely to receive treatment for caries [22].…”
Section: Discussionmentioning
confidence: 99%